Kirk-Othmer Encyclopedia of Chemical Technology 2004
DOI: 10.1002/0471238961.0825041819030809.a01.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine and Its Derivatives

Abstract: Hydrazine (diamide), N 2 H 4 , a colorless liquid having an ammoniacal odor, is the simplest diamine and unique in its class because of the NN bond. Hydrazine and its simple methyl and dimethyl derivatives have endothermic heats of formation and high heats of combustion. Hence, these compounds are used as rocket fuels. Other derivatives are used as gas generators and explosives. Hydrazine, a base slightly weaker than ammonia, forms a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
56
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 74 publications
0
56
0
1
Order By: Relevance
“…Hydrazine and hydrazine-based fuels such as monomethyl hydrazine are more commonly used as bipropellants with N 2 O 5 as the oxidizer. Hydrazine is used in thruster engines for attitude and in-orbit control of satellites and spacecraft, 1 where it is being stored and utilized at a maximal pressure of about 25 bar. [5][6][7] No detailed kinetic models for hydrazine-based fuels combustion in N 2 O 5 exist in the current literature; a step towards this goal is understanding hydrazine decomposition better.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazine and hydrazine-based fuels such as monomethyl hydrazine are more commonly used as bipropellants with N 2 O 5 as the oxidizer. Hydrazine is used in thruster engines for attitude and in-orbit control of satellites and spacecraft, 1 where it is being stored and utilized at a maximal pressure of about 25 bar. [5][6][7] No detailed kinetic models for hydrazine-based fuels combustion in N 2 O 5 exist in the current literature; a step towards this goal is understanding hydrazine decomposition better.…”
Section: Introductionmentioning
confidence: 99%
“…Substituted hydrazines have found many scientific and commercial applications 1, 2. The importance of hydrazine derivatives is reflected in the great number of such compounds synthesized to date, and the synthesis of substituted hydrazines has been the subject of many studies 3–6.…”
Section: Introductionmentioning
confidence: 99%
“…An alkaloid containing a hydrazone has also been isolated from a marine sponge (18). Hydrazones also involve many chiral building blocks, and they are applied in the agrochemical, pharmaceutical, and chemical industries (15). Hydrazones with replacement of R 2 and R 3 with hydrogen atoms, as used herein, involve many synthetic and natural compounds (9,15,18), but most of their physiological roles and biosynthetic mechanisms are unknown.…”
mentioning
confidence: 99%
“…Hydrazones also involve many chiral building blocks, and they are applied in the agrochemical, pharmaceutical, and chemical industries (15). Hydrazones with replacement of R 2 and R 3 with hydrogen atoms, as used herein, involve many synthetic and natural compounds (9,15,18), but most of their physiological roles and biosynthetic mechanisms are unknown. We recently found that the yeast Candida palmioleophila MK883 produces hydrazone dehydrogenase (HDH) and assimilates hydrazones, such as adipic acid bis(ethylidene hydrazide) (AEH) and valeric acid ethylidene hydrazide (VEH) (3).…”
mentioning
confidence: 99%